Efficient recovery and structural characterization of lignin from cotton stalk based on a biorefinery process using a γ-valerolactone/water system. Issue 8 (14th January 2016) - Wu, Miao; Liu, Jia-Kun; Yan, Zhong-Ya; Wang, Bo; Zhang, Xue-Ming; Xu, Feng; Sun, Run-Cang
Abstract : Lignin component (35.7–64.7%) was recovered by the pretreatment using γ-valerolactone/water system under different ratios of GVL to water. Abstract : In order to understand the integrated reaction behavior for biomass pretreatment using the γ-valerolactone (GVL)/water system, the recovery and structural changes of the lignin components from cotton stalk obtained under different ratios of GVL to water were investigated. Structural elucidation of these lignin samples was performed by Fourier transform infrared spectroscopy (FT-IR), high-performance anion-exchange chromatography (HPAEC), gel permeation chromatography (GPC), 2D heteronuclear single quantum coherence spectroscopy nuclear magnetic resonance (2D HSQC NMR), and derivatization followed by reductive cleavage (DFRC). The results showed that the separated lignin fractions possessed higher yields and purities than milled wood lignin (MWL). From the results of molecular weight, DFRC and 2D NMR analysis, it was also found that the lignin component from cotton stalk was a G–S type unit analogous to hardwood, and remarkable degradation and repolymerization occurred on lignin in this acid system, which led to more condensed and lower molecular weight lignin than MWL. Particularly, under the condition of GVL/H2 O 80/20, the cleavages of aryl-ether bonds dramatically happened, resulting in the least amount of β- O -4′ linkages. Considering the concept of biorefinery, the one-pot acid GVL/H2 O system with 80/20 GVL/H2 O could be an attractive method for the simple and efficient recovery of lignin and sugars simultaneously from agricultural wastes.